Dampak Minimarket (Alfamart Dan Indomaret) terhadap Tingkat Pengeluaran dan Pola Konsumsi Masyarakat di Kecamatan Kertak Hanyar - Hadi, Saptian (PPJP ULM, 2018)
This research is conducted to know: (1) minimarket impact on society expenditurelevel in Kecamatan Kertak Hanyar. (2) change of social consumption pattern after theminimarket. The analysis method used is a paired t-test. The research variable is thelevel of public expenditure before and after there minimarket in Kecamatan KertakHanyar. The data source is the primary data obtained through direct interviews withthe people who shop in the minimarket using questionnaires. The results of thecalculation using paired t-test showed a decrease in the expenditure level of theshopping community in the traditional market after the minimarket and the shift ofconsumption patterns from the conventional market to the minimarket.